A case of acute kidney injury from crystal nephropathy secondary to pomalidomide and levofloxacin use. (April 2016) - Baird, Phylicia; Leung, Sam; Hoang, Huy; Babalola, Olawumi; Devoe, Craig E; Wanchoo, Rimda; Jhaveri, Kenar D
Pomalidomide is an analog of thalidomide with immunomodulatory, anti-angiogenic, and anti-neoplastic activity indicated for the treatment of multiple myeloma refractory to at least two prior therapies. The incidence for renal failure was <5% in a single phase II study of pomalidomide and dexamethasone in patients with multiple myeloma that failed both lenalidomide and bortezomib therapy. We report a case suggesting crystal nephropathy as the mechanism for acute kidney injury in pomalidomide and fluoroquinolone use.